PHYSIOTHERAPY'S METHODOLOGY OF TESTING FOR PATIENTS WITH FAMILIAL AMYLOID POLYNEUROPATHY - Mariela Filipova; Daniela Popova; Stanislava Bogomilova; Gergana Nenova; David Kantchev (Peytchinski Publishing, 2020)
Familial amyloid polyneuropathy is a disease that occurs in southwestern Bulgaria. It causes a severe disability. The clinical picture is accompanied by weight loss, a muscle weakness, a cardiomyopathy and damage to the peripheral nervous system. The onset of symptoms is at a relatively early age (45-50 years). Specialists from Alexandrovska Hospital monitor patients with this type of disease. Purpose: The aim of the study is to create a kinesitherapeutic algorithm for the study of patients with familial amyloid polyneuropathy. Methods: The review study was undertaken in the Neurology department at Multidisciplinary hospital for active treatment- Blagoevgrad, Bulgaria. The study was conducted for the period 2015-2017, during which 10 patients with FAP were examined. In our algorithm we have included manual-musculе testing (ММТ) of the upper and lower limbs, an centimeter testing to measure hypotonia and a discriminant test to detect sensory disturbances. Results: The study involved 6 women and 4 men. The average age of the studied contingent is 48.0 ± 12.7 years. In the study we found that there is a change in the study of manual muscle testing. One unit increase available. There are no statistically significant differences in the study of centimeter in the lower extremities and in the study of the senses as well. Severe muscular hypotension and distal hypoesthesia persist. Conclusion: Unfortunately, these patients often progress rapidly. They remain disabled. Kinesitherapy, with its methods, can improve the quality of life.